BS40 High resolution single cell analysis of the developing human heart. (6th June 2022) - Bayraktar, Semih; Colzani, Maria; Davaapil, Hongorzul; Knight-Schrijver, Vincent; Rericha, Patrick; Lee, Jonathan Chuo Min; He, Xiaoling; Gambardella, Laure; Sinha, Sanjay
Abstract : The human heart is composed of various cell types with distinct embryonic origins and functions. Having an understanding of the components of the developing heart at a molecular level should provide better insights into its function in health and disease. Current single cell studies of human fetal hearts are limited by low cell numbers and poor cell type resolution. Here, we aimed to increase the number of cells studied while adding a spatial resolution. We analysed human hearts aged between post conception weeks of 8 and 11, where apex and base in each were processed, providing spatial resolution on cells constituting the myocardium and the great vessels. Our analysis suggests 6 main cell types in the developing hearts with a total of 28 subtypes and provides a differential expression signature for similar cell types with different origins and anatomical locations, including the smooth muscle cells and endothelial cells of the myocardium and the great vessels. Through immunohistochemistry, we validated our findings on these subtypes, as well as on the cells that were less clearly described before, such sinoatrial node cells or resident macrophages. Cell to cell interaction analysis inferred distinct molecular crosstalk across subtypes, including the cells of the great vessels or the vessels of the myocardium. Our findings suggest a list of transcription factors that might be involved in governing the identity of these cells. Collectively, our analysis provides a better understanding of human heart development, and will inform studies into disease modelling and disease progression.